2016
DOI: 10.1038/onc.2016.301
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the RP-MDM2-p53 pathway accelerates APC loss-induced colorectal tumorigenesis

Abstract: Inactivation of the adenomatous polyposis coli (APC) tumor suppressor is frequently found in colorectal cancer. Loss of APC function results in deregulation of the Wnt/β-catenin signaling pathway causing overexpression of the c-MYC oncogene. In lymphoma, both p19ARF and ribosomal proteins RPL11 and RPL5 respond to c-MYC activation to induce p53. Their role in c-MYC-driven colorectal carcinogenesis is unclear, as p19ARF deletion does not accelerate APC loss-triggered intestinal tumorigenesis. To determine the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
(70 reference statements)
1
19
0
1
Order By: Relevance
“…The deregulation of the Wnt/β-catenin signaling pathway in human cancer has been attributed to the inactivation of APC tumor suppressor ( Sansom et al, 2004 ). A recent study has indicated that the ribosomal protein-MDM2-p53 pathway is another crucial mediator of APC loss-induced tumorigenesis ( Liu et al, 2017 ). Herein, dual inhibition of β-catenin and MDM2 may display a synergistic anticancer activity and could be a promising therapeutic strategy for advanced pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The deregulation of the Wnt/β-catenin signaling pathway in human cancer has been attributed to the inactivation of APC tumor suppressor ( Sansom et al, 2004 ). A recent study has indicated that the ribosomal protein-MDM2-p53 pathway is another crucial mediator of APC loss-induced tumorigenesis ( Liu et al, 2017 ). Herein, dual inhibition of β-catenin and MDM2 may display a synergistic anticancer activity and could be a promising therapeutic strategy for advanced pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Also, disparity between our findings on SW13 and H295R cells supports the notion, as those cells represent different types of adrenocortical cancer. Our findings also raise questions regarding crosstalk between canonical Wnt signaling and MDM2, which are previously suggested to be very loosely connected . Scholars suggest disruption of the RP‐MDM2‐p53 pathway accelerates APC loss‐induced colorectal tumorigenesis, yet how much APC loss can simulate CTNNB1 mutation in the ACC context remains undetermined.…”
Section: Discussionmentioning
confidence: 73%
“…APC loss of function, especially due frameshift and nonsense mutations, or down-regulation is a major cause in the colorectal tumorigenesis and it’s been proposed its loss is sufficient to induce carcinogenesis [ 42 , 43 ]. Our results indicate that APC down-regulation is also an important risk factor to the development of gastric cancer and that this gene may have a crucial function in gastrointestinal malignant neoplasia.…”
Section: Discussionmentioning
confidence: 99%